Model Leadership Style Governor Kepulauan Riau Province During Covid-19 Pandemic in Indonesia - Fitri Kurnianingsih; Lamidi Lamidi; Oksep Adhayanto; Mahadiansar Mahadiansar; Rio Yusri Maulana (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Model The leadership style of regional heads during the COVID-19 pandemic requires a compelling lead character because to deal with the problems felt by each region, and it must be different so that public responses and criticisms must be carried out quickly and accurately has a priority scale for work effectiveness. Novelty: This study analyzes the leadership style of the regional head in Indonesia, namely the Governor, by taking a case study in the Riau Islands Province (Kepri) during the COVID pandemics. Research Method: The research method used is qualitative with relevant secondary data. Finding/Results: The results of data analysis with software NVivo 12, so that obtained are easy to explain descriptively by analyzing the theory and concept triangulation approach. Conclusion: The results show that the determination of Secondary Data Coding is more on the leadership of Ansar Ahmad in the COVID-19 pandemic as Governor Kepri. In addition, researchers also found that Ansar Ahmad’s leadership style as Governor Kepri greatly influenced the characteristics of leadership style and influential leadership style, which tested with the Jaccard Cluster approach on the strong relationship between communication, awareness, and integrity in carrying out the vision and mission as regional head during a COVID-19 in Kepri Province.